Studies of Decomposition rate and release of nutrients Ammonium, Nitrates, Nitrites, and Phosphatesions during the decomposition of Oryza coarctata in the laboratory experiment. - Zafar Farooqui; Pirzada Jamal Siddiqui; Seema Shafique; Munawwer Rasheed (Journal of Tropical Life Science, 2013)
he vegetation, other than the mangroves in Indus delta, for example Oryza coarctata is also the source of nutrients for the adjacent coastal environment. The O. coarctata is the major vegetation on the tidal mudflatds of Keti- Bunder (Hajambro creek), Indus delta, other than the Avicennia marina and Rhizophora mucronataplanted mangrove forest. This is the first report of decomposition rates of O. coarctata in the laboratory. The decomposition of O. coarctata. was conducted to evaluate the nutrients (ammonium, nitrate, nitrites, phosphates) during the decomposition. The decomposition rate was more rapid during this early phase and O. coarctata. decomposed up to 40 % during the first 7 days. Afterwards, the Oryzasp. decomposed slowly and gradually and remained up to 40% of the dry mass. Therefor e, about 60% of the organic matter present in the O. coarctatacan decompose completely in the aerobic conditions of the aquatic environment. The ammonium ions concentration was found 2.75 Î¼M/L at 7th day and highest value was 6.38 Î¼M/L at 124th day of exp eriment. So the amount of ammonium ions increased during the phase of decomposition. The nitrate ions concentration was 1.95 Î¼M/L at 7th day and increased to 2.71 Î¼M/L at 15th day of decomposition, and afterwards the concentration of nitrate decreased gradually and lowest value 0.129 Î¼M/L was recorded in the last day of the experiment. The nitrite ions concentration was found 1.80 Î¼M/L and gradually increased to 3.33 Î¼M/L at 60th day and the lowest value was 3.05 Î¼M/L. The initial concentration of the phosphate ions was 0.84 and decresed gradually during the phase of decomposition to its lowest value at 0.7 Î¼M/L. The concentration of the nitrogen in the O. coarctata was initially between 1- 1.5 mg DW, which increased to about 2 mg DW at the 7th day of the decomposition. The % DW nitrogen contents than decreased suddenly at 15th day reaching up to about 1 mg DW of the decomposed material. This decrease of the t otal DW Nitrogen is very important, as it is the source of the nutrients to the adjacent ecosystem. The results are also strongly correlated with the nutrients values.